IscS Functions as a Primary Sulfur-donating Enzyme by Interacting Specifically with MoeB and MoaD in the Biosynthesis of Molybdopterin in Escherichia coli - Zhang, Wanjiao (American Society for Biochemistry and Molecular Biology, 2010)
The persulfide sulfur formed on an active site cysteine residue of pyridoxal 5′-phosphate-dependent cysteine desulfurases is subsequently incorporated into the biosynthetic pathways of a variety of sulfur-containing cofactors and thionucleosides. In molybdenum cofactor biosynthesis, MoeB activates the C terminus of the MoaD subunit of molybdopterin (MPT) synthase to form MoaD-adenylate, which is subsequently converted to a thiocarboxylate for the generation of the dithiolene group of MPT. It has been shown that three cysteine desulfurases (CsdA, SufS, and IscS) of Escherichia coli can transfer sulfur from l-cysteine to the thiocarboxylate of MoaD in vitro. Here, we demonstrate by surface plasmon resonance analyses that IscS, but not CsdA or SufS, interacts with MoeB and MoaD. MoeB and MoaD can stimulate the IscS activity up to 1.6-fold. Analysis of the sulfuration level of MoaD isolated from strains defective in cysteine desulfurases shows a largely decreased sulfuration level of the protein in an iscS deletion strain but not in a csdA/sufS deletion strain. We also show that another iscS deletion strain of E. coli accumulates compound Z, a direct oxidation product of the immediate precursor of MPT, to the same extent as an MPT synthase-deficient strain. In contrast, analysis of the content of compound Z in ΔcsdA and ΔsufS strains revealed no such accumulation. These findings indicate that IscS is the primary physiological sulfur-donating enzyme for the generation of the thiocarboxylate of MPT synthase in MPT biosynthesis.